True west : Sam Shepard's life, work, and times - Greenfield, Robert (Crown, 2023)
"An intimate portrait of the iconic playwright, actor, and director Sam Shepard, whose wide-ranging and enduring body of work places him at the center of the American canon, from an award-winning biographer. True West is the story of an American icon, a lasting portrait of Sam Shepard as he really was, revealed by those who knew him best. This sweeping biography charts Shepard's long and complicated journey from a small town in southern California to his standing as an internationally known playwright and movie star. The son of an alcoholic father, Shepard crafted a public persona as an authentic American archetype: the loner, the cowboy, the drifter, a stranger in a strange land. Despite his great critical and financial success, he seemed, like so many of his characters, to remain perpetually dispossessed. Much like Robert Greenfield's biographies of Jerry Garcia and Timothy Leary, this book delves deeply into Shepard's life as well as the ways in which his work illuminates it. True West takes readers through the world of downtown theater in lower Manhattan in the early sixties, the jazz scene at the Village Gate, fringe theatre in London in the seventies, Bob Dylan's legendary Rolling Thunder tour, the making of classic films like Zabriskie Point, Days of Heaven, and The Right Stuff, and Broadway productions of Buried Child, True West, and Fool for Love. For this definitive biography, Greenfield interviewed dozens of people who knew Shepard well, many of whom had never before spoken on the record about him. While exploring his relationships with Patti Smith, Bob Dylan, Joni Mitchell, and Jessica Lange across the long arc of his brilliant career, Greenfield makes the case for Shepard not just as a great American writer but a unique figure who first brought the sensibility of rock 'n' roll to serious theater"--